Seed potato production. - Davidson, R.D.; Xie, K. (CAB International, 2014)
This chapter compares the formal versus informal method of seed potato production, and describes the true potato seed as well as the diseases and pests of concern. The certification process, sanitation and the early-generation stocks are discussed. Seed potato production is a complicated business. To be successful, there are basic guidelines one must follow, whether using an informal grower-saved seed source or a more formal certification programme. Production of disease-free, high-quality seed potatoes is the first and most important component in the production of high-quality, high-yielding table-stock potatoes. Poor seed quality can financially ruin commercial producers, reduce the food supply, and damage an industry.